2018
DOI: 10.2478/humo-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aerobic capacity and energy expenditure in folk dancers

Abstract: Purpose. The aim of the study was to evaluate the aerobic capacity and energy expenditure of folk dancers. Methods. The aerobic capacity (VO 2max ) of four male and four female folk dancers was measured by an incremental treadmill test and energy expendi ture was assessed by the linear relationship between heart rate and oxygen uptake as based on indirect calorimetry. , respectively. Conclusions. The exercise intensity performed during folk dancing is close to the threshold of decompensated metabolic acidosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…Other researchers reached similar conclusions [5,20,24]. Liiv et al [19] postulated that a high level of aerobic capacity is essential to competing in sports dance at the highest level.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Other researchers reached similar conclusions [5,20,24]. Liiv et al [19] postulated that a high level of aerobic capacity is essential to competing in sports dance at the highest level.…”
Section: Discussionsupporting
confidence: 66%
“…Liiv et al [19] postulated that a high level of aerobic capacity is essential to competing in sports dance at the highest level. Maciejczyk and Feć [20] made similar observations in their paper on folk dancers. The also stressed the necessity of shaping both aerobic and anaerobic characteristics of physical capacity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The mean values of VO 2peak found in the current study are in accordance with the previous values reported for male folk dancers, namely 43.5 ml.kg.dk −1 [8], 51.8 ml.kg. dk −1 [19], and 45.3 ml.kg.dk −1 [20]. However, the VO 2peak values of male dancers of 30 top class dancesport couples (12 Standard, 7 Latin American, and 11 Ten Dance) were higher (59.2-60.9 ml.kg.dk −1 ) than the VO 2peak values of male folk dancers [8,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…dk −1 [19], and 45.3 ml.kg.dk −1 [20]. However, the VO 2peak values of male dancers of 30 top class dancesport couples (12 Standard, 7 Latin American, and 11 Ten Dance) were higher (59.2-60.9 ml.kg.dk −1 ) than the VO 2peak values of male folk dancers [8,19,20]. The difference may be due to the dancers' international level and higher aerobic capacity requirement of dancesport compared to other dance forms [21].…”
Section: Discussionmentioning
confidence: 99%